Implications of Local Knowledge Construction in Empowerment Practices of Women's Groups at Batik Liza Mangrove Studio, Pematang Johar Village, Deli Serdang Regency - Mujahiddin Mujahiddin; Yurisna Tanjung; Nurhasanah Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
At present, the global development goals stated in the Sustainable Development Gols (SDGs), the empowerment agenda is still the main focus, especially with regard to empowering women's groups. Although it does not explicitly emphasize women's empowerment in it, in many cases community empowerment practices through ADD always place poor and under-prosperous women as the main participants. In Pematang Johar Village, Deli Serdang Regency, the practice of empowering women's groups is carried out by developing entrepreneurship based on the local potential of the village, namely through batik crafts. This program begins with the formation of a women's batik group with the aim that the batik group formed can produce batik works with local characteristics which are then given the name "Batik Sawah". The research design used a qualitative research design with a case study approach to a group of women in the Batik Liza Mangrove Studio, Pematang Johar Village, Deli Serdang Regency. The data in this study were collected using in-depth interviews with each research informant. The research informants were selected using a purposive sampling approach. Based on the results of the discussion above, it can be concluded that the batik training given to the women's batik groups makes them self-empowered in the form of authority, knowledge and abilities. This condition makes them able to fulfill their daily needs physically, economically and socially. The impact of the practice of empowering women at the Liza Manggrove Batik Studio has only succeeded in improving family welfare subjectively. This is because the income generated from batik activities can only be used to meet the primary needs of the family and has not been able to meet other needs.